2000
DOI: 10.1093/toxsci/58.2.324
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin Inhibits Luminal Cell Differentiation and Androgen Responsiveness of the Ventral Prostate without Inhibiting Prostatic 5alpha-Dihydrotestosterone Formation or Testicular Androgen Production in Rat Offspring

Abstract: In utero and lactational exposure to a single maternal dose of 1 microg 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)/kg causes some overt toxicity and impairs prostate growth in male offspring. As similar effects on the ventral prostate can be caused by decreased testosterone production during perinatal development, we determined whether intratesticular testosterone content, testicular responsiveness to gonadotropin stimulation, or plasma testosterone concentrations were reduced in fetal and newborn rats. Becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Prostate DHT was extracted by the method of Theobald et al (42). Briefly, homogenates were extracted twice with 10 volumes of anhydrous ethyl ether.…”
Section: Methodsmentioning
confidence: 99%
“…Prostate DHT was extracted by the method of Theobald et al (42). Briefly, homogenates were extracted twice with 10 volumes of anhydrous ethyl ether.…”
Section: Methodsmentioning
confidence: 99%
“…Among the reproductive endpoints affected, the reduced ventral prostate weight was sensitive and consistent with previous studies using the same experimental protocol. Effects of in utero TCDD exposure on the development of ventral prostate were intensively studied (26)(27)(28)(29)(30). It is suggested that TCDD exposure impairs prostate growth and androgen responsiveness by inhibiting prostatic epithelial cell differentiation (28).…”
Section: Non-pregnant Ratsmentioning
confidence: 99%
“…Interactive effects of TCDD and DDE on male reproductive tract development were also observed in rats suggesting that exposure to both these chemicals may potentiate their individual actions although by different mechanism since DDE is not an Ah-receptor agonist (Loeffler and Peterson, 1999). Other studies suggest that TCDD exposure impairs prostate growth and androgen responsiveness by inhibiting prostatic epithelial cell differentiation and morphogenesis (Theobald et al, 2000;Ko et al, 2002;Timms et al, 2002).…”
Section: Introductionmentioning
confidence: 97%